Relationship Between the Police Educational Formation System and Public Security - Beu, Artur; Nepravishta, Ariana (European Journal of Sustainable Development, 2013)
The harmonization between the Albanian police education system and the EuropeanFramework and in particular with the Bologna System is a must of nowadays and for thepolice organization itself. In this context, the police organization needs to be upgradeespecially in the upper level but it can’t be understood without an adequate educationalsystem. Currently, the challenges of the police education system face some obstacles offormation type which lead to a lack in the police education to achieve university levels.This will return into a boomerang for the forthcoming generations which are beingprepared to be police staff, due to the lack of relevant university education. Based on thecurrent education model, a police officer recruit has the opportunity to joint policeorganization after the high school (18 years old), and his education level is destined to benot upgraded in any way in order to reach university levels. It seems that Albania has somuch need to an escalation process when it comes to the police education system that itcan accept a missing formation which could lead to real problems in the near future. Thistype of model could function in the basic operational level but it is destined tomalfunction in the upper level of leadership. In this contexts it is needed a paralleluniversity education level associated to the police education formation in order toupgrade the police leadership. Currently, there is no experience of cooperation betweenuniversities and police formation institution in this regard. In Europe and other countriesof the Region the main goal is the unification of curricula in order to have some commoncore curricula and in this manner to improve the mutual exchange of students and cadetsfrom one to another institution and from one to another country. This is absolutelyachievable also in police education and formation framework. A more effectivecooperation and exchange process of students among police academies and formationcenters in Europe and region will enable a more effective fight against crime and will leadto the so desirable product of enhancement of public trust towards police and an increaseof the perception of security.